Relationship of leptin with insulin indices in gestational diabetes mellitus - Mohana, Choman Abdullah; Paul, Susmita; Morshed, Md Shahed; Jahan, Sharmin; Tofail, Tania; Saleh, Ahmed Abu; Hasanat, Muhammad Abul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Leptin is thought to increase and affect glucose and insulin homeostasis in gestational diabetes mellitus (GDM). Objectives: To see the relationships among leptin, insulin indices (homeostatic model of insulin assessment, HOMA-IR), and obesity among women with GDM. Methods: Women (n=107) with 24-28 weeks gestation were tested by 75 gm oral glucose (OGTT) to divide into GDM [n=45, age: 27.80±3.98 years, mean±SD; BMI: 27.88(24.46, 30.43) kg/m2, median] and normal glucose tolerance [NGT; n=62, age: 26.19±5.30 years, mean±SD; BMI: 25.80(23.65,28.42) kg/m2, median] following WHO-2013 diagnostic criteria. Fasting plasma glucose, insulin, and leptin were measured by glucose oxidase and ELISA methods respectively. Results: Glucose values (fasting, 01h, and 02h; mmol/L) were significantly higher in GDM than those of NGT in both subgroups of HOMA-IR [≥2.89: insulin resistant (IR), <2.89: insulin sensitive (IS)]. BMI was significantly higher in GDM with IR than that of GDM with IS whereas fasting insulin in both the HOMA-IR subgroups of GDM as well as of NGT differed significantly. None of the BMI nor glucose values of OGTT or fasting insulin correlated significantly with leptin either in GDM or in NGT in the subgroup with IR; whereas in the IS-subgroup, BMI, 01hG, 02hG, and fasting insulin correlated significantly in NGT only. ROC curve analysis for leptin revealed it as an unreliable marker of IR (AUC = 0.553) in GDM. Conclusions: Serum leptin does not correlate with insulin indices in GDM. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2023; 2 (2):46-51